Association between implementation of novel therapies and improved survival in patients starting haemodialysis: the Swedish Renal Registry 2006–15. Issue 7 (16th December 2020) - Evans, Marie; Xu, Hong; Rydell, Helena; Prütz, Karl-Göran; Lindholm, Bengt; Stendahl, Maria; Segelmark, Mårten; Carrero, Juan-Jesus
Abstract: Background: The recent years have witnessed significant therapeutic advances for patients on haemodialysis (HD). We evaluated temporal changes in treatments practices and survival rates among incident HD patients. Methods: This was an observational study of patients initiating HD in Sweden in 2006–15. Trends of HD-related practices, medications and routine laboratory biomarkers were evaluated. The incidence of death and major cardiovascular events (MACEs) across calendar years were compared against the age- and sex-matched general population. Via Cox regression, we explored whether adjustment for implementation of therapeutic advances modified observed survival and MACE risks. Results: Among 6612 patients, age and sex were similar, but the burden of comorbidities increased over time. The proportion of patients receiving treatment by haemodiafiltration, ≥3 sessions/week, lower ultrafiltration rate and working fistulas increased progressively, as did use of non-calcium phosphate binders, cinacalcet and vitamin D3. The standardized 1-year mortality decreased from 13.2% in 2006–07 to 11.1% in 2014–15. The risk of death decreased by 6% [hazard ratio (HR) = 0.94, 95% confidence interval (CI) 0.90–0.99] every 2 years, and the risk of MACE by 4% (HR = 0.96, 95% CI 0.92–1.00). Adjustment for changes in treatment characteristics abrogated these associations (HR = 1.00, 95% CI 0.92–1.09 for death and 1.00, 0.94–1.06 for MACE). Compared with the general population, the risk of death declined from 6 times higher in 2006–07 [standardized incidence rate ratio (sIRR) = 6.0, 95% CI 5.3–6.9] to 5.6 higher in 2014–15 (sIRR = 5.57, 95% CI 4.8–6.4). Conclusions: Gradual implementation of therapeutic advances over the last decade was associated with a parallel reduction in short-term risk of death and MACE among HD patients.